3,4-Dibromo-2,5-dimethyl-1-phenylsulfonyl-1H-pyrrole - J. Kanchanadevi; G. Anbalagan; R. Sureshbabu; A. K. Mohanakrishnan; V. Manivannan (Acta Crystallographica Section E, 2011)
In the title compound, C12H11Br2NO2S, the dihedral angle between the two rings is 78.79 (12)°. The crystal packing features C—H...π interactions.